Toward the Deepening of Democracy in Indonesia: Assessing the Prospects and Problems from a Habermasian Perspective - Fatlolon, Constantinus (Archīum Ateneo, 2024)
From the perspective of Habermas’s theory of law and democracy, Indonesia’s democratic project will require the “reformation” of political institutions and the development of its citizens’ democratic consciousness. The former can be achieved through constitutional amendments while the latter is mediated by civil society and non-governmental organizations. To bridge the gap between the democratically oriented provisions of the constitution and the non-democratic practices of those who govern Indonesian society, political structures and procedures that recognize the equal rights and the autonomy of the citizenry must be installed. The deliberative principles embedded in Pancasila, the state’s official philosophy, can be harnessed in order to institutionalize and hasten the processes of democratization in Indonesia.